A COMPARATIVE STUDY ON THE EFFECTIVENESS OF ADDING ROSEMARY AND GINGER EXTRACTS ON MEAT QUALITY DURING FREEZING STORAGE - & Alkass, Baker (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The aim of the this experiment was to  determine the effect of adding rosemary (0.05%)and ginger extracts (0.5%) on microbial and oxidative stability in meat lamb  stored at -18º c for 150 days.  Results revealed that there is steady rise (p